MiR‐219a‐5p Regulates Rorβ During Osteoblast Differentiation and in Age‐related Bone Loss. (15th October 2018) - Aquino‐Martinez, Ruben; Farr, Joshua N; Weivoda, Megan M; Negley, Brittany A; Onken, Jennifer L; Thicke, Brianne S; Fulcer, McKenzie M; Fraser, Daniel G; van Wijnen, Andre J; Khosla, Sundeep; Monroe, David G
ABSTRACT: Developing novel approaches to treat skeletal disorders requires an understanding of how critical molecular factors regulate osteoblast differentiation and bone remodeling. We have reported that (1) retinoic acid receptor‐related orphan receptor beta (Rorβ) is upregulated in bone samples isolated from aged mice and humans in vivo; (2) Rorβ expression is inhibited during osteoblastic differentiation in vitro; and (3) genetic deletion of Rorβ in mice results in preservation of bone mass during aging. These data establish that Rorβ inhibits osteogenesis and that strict control of Rorβ expression is essential for bone homeostasis. Because microRNAs (miRNAs) are known to play important roles in the regulation of gene expression in bone, we explored whether a predicted subset of nine miRNAs regulates Rorβ expression during both osteoblast differentiation and aging. Mouse osteoblastic cells were differentiated in vitro and assayed for Rorβ and miRNA expression. As Rorβ levels declined with differentiation, the expression of many of these miRNAs, including miR‐219a‐5p, was increased. We further demonstrated that miR‐219a‐5p was decreased in bone samples from old (24‐month) mice, as compared with young (6‐month) mice, concomitant with increased Rorβ expression. Importantly, we also found that miR‐219a‐5p expression was decreased in aged human bone biopsies compared with young controls, demonstrating that this phenomenon also occurs in aging bone in humans. Inhibition of miR‐219a‐5p in mouse calvarial osteoblasts led to increased Rorβ expression and decreased alkaline phosphatase expression and activity, whereas a miR‐219a‐5p mimic decreased Rorβ expression and increased osteogenic activity. Finally, we demonstrated that miR‐219a‐5p physically interacts with Rorβ mRNA in osteoblasts, defining Rorβ as a true molecular target of miR‐219a‐5p . Overall, our findings demonstrate that miR‐219a‐5p is involved in the regulation of Rorβ in both mouse and human bone. © 2018 American Society for Bone and Mineral Research.